2008
DOI: 10.1051/meca:2008028
|View full text |Cite
|
Sign up to set email alerts
|

Analyse des pertes de puissance dans les transmissions par engrenages

Abstract: BOTTA-ZIMMERMANN M. (Mme) UNITE DE RECHERCHE EN GENIE CIVIL-Développement Urbain BOULAYE G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Experiments have still shown that WPL value is modified when helix angle value becomes not null. For example Dawson (2) noticed a decrease of WPL when the helix angle of large width gears is increased whereas opposite observation was made in Diab et al investigation (8) when using highly different gear characteristics. More investigations are therefore needed to better understand the contribution of helix angle in WPL if appropriate model is wanted.…”
Section: Introductionmentioning
confidence: 92%
“…Experiments have still shown that WPL value is modified when helix angle value becomes not null. For example Dawson (2) noticed a decrease of WPL when the helix angle of large width gears is increased whereas opposite observation was made in Diab et al investigation (8) when using highly different gear characteristics. More investigations are therefore needed to better understand the contribution of helix angle in WPL if appropriate model is wanted.…”
Section: Introductionmentioning
confidence: 92%